Prevalence and Antimicrobial Susceptibility Patterns of Wound and Pus Bacterial Pathogens at a Tertiary Care Hospital in Central Riyadh, Saudi Arabia - Fizza Khalid; Christy Poulose; Dalal Farah Mousa Farah; Abid Mahmood; Azza Elsheikh; Osamah T. Khojah (Microbiology Research)
The long history and extensive use of antibiotics have caused resistant bacterial pathogens to emerge, increasing mortality and morbidity. The current study was designed to see the prevalence of aerobic bacterial isolates with their antimicrobial resistance pattern from out- and inpatients requested for wound or pus culture. Retrospective study conducted at a tertiary care hospital in central Riyadh from January 2023 to December 2023. Samples were collected and inoculated onto the appropriate media following standard guidelines. Bacterial pathogens were identified by the Vitek2 compact system. Antimicrobial susceptibility was tested using the Kirby–Bauer disk diffusion method as well as by MIC determination through the Vitek2 compact. A total of 1186 subjects were included in the study with a bacterial isolation rate of 691 (58.3%). Out of these, 155 positive cultures had incomplete information or anaerobic or fungal growth and were excluded from the study. With a slight female predominance (54.9%), the majority of subjects (72.2%) were outpatients, and over half of the isolates (55.2%) were Gram-positive. The most common isolate was Staphylococcus spp. (44.4%), followed by E. coli (13.6%) and P. aeruginosa (12.9%). The highest resistance was reported against penicillin followed by fusidic acid against Gram-positive bacteria. Methicillin-resistant Staphylococcus aureus (MRSA) was detected in 40.5% of Staphylococcus aureus (S. aureus) isolates. Amikacin was the most susceptible antibiotic against all Gram-negative isolates. MDR Gram-negative bacteria accounted for 51.9% of wound infection isolates (95% CI: 45.95 to 58.33) while 6.3% (95% CI: 4.39 to 8.86) were XDR (nonsusceptibility to at least one agent in all but two or fewer antimicrobial categories). A high prevalence of bacterial isolates, with S. aureus as the predominant pathogen, showed high rates of multidrug resistance. This highlights the importance of monitoring antibiotic choices for prophylaxis and treatment in the study area.